Densities at high pressures and derived properties of thiophenes. (June 2017) - Antón, V.; Lomba, L.; Cea, P.; Giner, B.; Lafuente, C.
Graphical abstract: Highlights: The pρT behaviour of four members of the thiophene family has been studied. The experimental results have been correlated with the TRIDEN equation. Isobaric expansibilities, isothermal compressibilities and internal pressures have been calculated. The results were discussed in terms of structural differences among thiophenes. Abstract: This contribution reports the densities in wide temperature (from 283.15 to 338.15 K) and pressure (from 0.1 to 65.0 MPa) ranges of four members of the thiophene family (thiophene, 2-methylthiophene, 3-methylthiophene and 2, 5-dimethylthiophene). These densities have been satisfactorily correlated by means of the TRIDEN equation. From these data, several derived properties as isobaric expansibility, isothermal compressibility, and internal pressure have been estimated. Using all these properties, interesting information about molecular organization can be deduced.